2019
DOI: 10.1111/cobi.13372
|View full text |Cite
|
Sign up to set email alerts
|

Predicting intervention priorities for wildlife conflicts

Abstract: There is growing interest in developing effective interventions to manage socially and environmentally damaging conservation conflicts. There are a variety of intervention strategies that can be applied in various contexts, but the reasons one type of intervention is chosen over another remain underexplored. We surveyed conservation researchers and practitioners (n = 427) to explore how characteristics of conflicts and characteristics of decision makers influence recommendations to alleviate conservation confl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…2016; Baynham‐Herd et al. 2019). Moreover, implementing mitigation strategies for only 1 species is unlikely to reduce potential negative attitudes toward wildlife in general if other species are also perceived to be a problem in the same area (Lescureux & Linnell 2010; Suryawanshi et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2016; Baynham‐Herd et al. 2019). Moreover, implementing mitigation strategies for only 1 species is unlikely to reduce potential negative attitudes toward wildlife in general if other species are also perceived to be a problem in the same area (Lescureux & Linnell 2010; Suryawanshi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, such multispecies, spatiotemporal assessments are absent from the literature, which has instead tended to focus on single species (e.g., Wilson et al 2015). This oversimplification of HWI situations risks hindering the development of cost-effective management strategies aimed at decreasing costs associated with living with wildlife (Kansky et al 2016;Baynham-Herd et al 2019). Moreover, implementing mitigation strategies for only 1 species is unlikely to reduce potential negative attitudes toward wildlife in general if other species are also perceived to be a problem in the same area (Lescureux & Linnell 2010;Suryawanshi et al 2013;Redpath et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are other calls for its continuation to support conservation efforts in specific contexts that preclude other options, and where program delivery is coherent, well administered, validated, and sustainable [5,8,[61][62][63]. Understanding and teasing out the factors that lead to success (or failure) of conservation interventions such as compensation schemes demands adequate monitoring and evaluation programs that capture both local perspectives of the target beneficiaries, and the full range of parameters influenced by the scheme, be they ecological, social or economic [36,64].…”
Section: Compensation Schemes and Their Evaluationmentioning
confidence: 99%
“…Human psychology, broader social norms, or policies in the community or region can all influence adaptation options, the ease of implementation, and likelihood of adoption (Bennett et al, 2017;van Eeden et al, 2018a,b). For example, it was found that conservation professionals favored enforcement and awareness adaptations when conflict was occurring in more highly developed countries (Baynham-Herd, Redpath, Bunnefeld, & Keane, 2019). Thus, lessons learned from sustainability science and transdisciplinary research are well suited to support human-wildlife coexistence research, practice, and policy.…”
Section: Moving Forwardmentioning
confidence: 99%